Pelatihan Pembuatan Nugget Ikan Louhan sebagai Upaya Pemberdayaan Ibu-Ibu Pondok Pesantren Al-Manshurin Jayapura - Kristina Haryati; Irja Sepriyanto Jenmau (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Louhan fish are predatory fish from Lake Sentani that can be processed into fishery products such as nuggets. Nuggets are created from a mixture of crushed fish meat, flour, and other ingredients, then coated with flour. This initiative aims to enhance the skills of partners in processing louhan fish into nugget products. The partners in this community service activity are mothers at the Al-Manshurin Islamic Boarding School in Waena, who lack creativity in processing louhan fish into various products. The challenge faced by the partners is a lack of knowledge regarding the louhan fish processing. Therefore, the solution provided is training in making louhan fish nuggets. The community service activity was conducted at the Al-Manshurin Islamic Boarding School, located in Waena, Jayapura City. The methods employed were socialization, practice, and evaluation. Twenty participants attended this community service activity. The participatory role of partners in this activity is to be actively involved in all stages, from socialization and practice to evaluation. The community service activities conducted by the team demonstrated a 100% increase in the skills of all mothers at the Al-Manshurin Waena Islamic Boarding School in making louhan fish nuggets after the processing practice.